trigonometry math Homework Help

We’ve answered 396,459 questions. We can answer yours, too.

eNotes Homework Help is a way for educators to help students understand their school work. Our experts are here to answer your toughest academic questions! Once it’s posted to our site, your question could help thousands of other students.

Showing All Questions Unanswered Answered Popular Recommended in trigonometry math

• trigonometry math
To find the distance from the vertex to the shoreline which will divide the lot into two equal parts, find the length of what would be the line dividing the lot. As we have 2 exisitng angles, find...

Asked by erwina on via web

1 educator answer.

• trigonometry math
tan a + cot a + tan 3a +cot 3a = 8 cos^2 2a/ sin 6a LHS=tan a+cot a + tan (3a) +cot (3a) =tan a + 1/ (tan a )+ tan (3a) + 1/ (tan (3a) ) =(tan^2(a)+1)/(tan(a))+ (tan^2(3a)+1)/(tan(3a))...

Asked by aisyah95 on via web

• Math
We wish to find the value of the expression ` ``sin((5pi)/3)` . The domain of `x` over one whole period of the sine function `sin(x)` is ` `0 to `2pi` . If we look at a graph of a single period...

Asked by yapayapa on via web

2 educator answers.

• Math
We wish to find the value of the expression `cos((23pi)/12)`. The domain of `x` over one whole period of the cosine function `cos(x)` is ` `0 to `2pi` . If we look at a graph of a single period of...

Asked by yapayapa on via web

2 educator answers.

• trigonometry math
One way to solve this problem is to use these identities: sin 2x = 2 sin x*cos x sin x = 2 tan(x/2)/[1+(tan x/2)^2] cos x = [1-(tan x/2)^2]/[1+(tan x/2)^2] We'll replace tan x/2 by t: sin x = 2...

Asked by chiefmit93 on via web

• trigonometry math
The expression you have provided is true because sin 2x = 2*sin x*cos x and cos 2x = (cos x)^2 - (sin x)^2 Let start with (cos x + sin x)/(cos x - sin x) multiply the numerator and denominator by...

Asked by cica777 on via web

1 educator answer.

• trigonometry math
We have to find the sum sin 135 + cos 150 Use the relations: sin (90 + x) = cos x and cos(180 - x) = -cos x sin 135 + cos 150 => sin (90 + 45) + cos (180 - 30) => cos 45 - cos 30 cos 45 =...

Asked by karladahl on via web

1 educator answer.

• trigonometry math
We'll manage the left side of the given expression: We know that cot (2x) = cos (2x)/sin (2x) We'll apply the double angle identities: cos (2x) = 1 - 2(sin x)^2 sin (2x) = 2sin x*cos x cot (2x) =...

Asked by articsonia on via web

• trigonometry math
First, we'll shift cos x to the right side: sqrt3*sin x = cos x We'll divide by cos x both sides: sqrt3*sin x/cos x = 1 But the fraction sin x/cos x can be replaced by the tangent function tan x....

Asked by doorsreb on via web

1 educator answer.

• trigonometry math
We have to prove that cos 2x * (1 + tan x*tan 2x) = 1 cos 2x = 1 - (sin x)^2 and tan 2x = 2*tan x/(1 - (tan x)^2) cos 2x * (1 + tan x*tan 2x) => ((cos x)^2 - (sin x)^2)*(1 + (tan x)*(2*tan x/(1...

Asked by lessoflot on via web

1 educator answer.

• trigonometry math
Well, you could use substitution technique. Let's see why and how to manage this technique. We notice that instead of the 1st term sin 2x, we can use the equivalent product, namely 2 sin x*cos x....

Asked by peux on via web

• trigonometry math
We'll write tan 2x as a sum of 2 equal angles. tan 2x = tan (x+x) tan 2x = (tan x + tan x)/[1 - (tan x)^2] tan 2x = 2tan x/[1 - (tan x)^2] (1) We know, from enunciation, the value of tan x = 2/3....

Asked by carrotpie on via web

• trigonometry math
We'll apply the Pythagorean identity to solve the equation: (sin x)^2 + (cos x)^2 = 1 We'll write (sin x)^6 + (cos x)^6 = ((sin x)^2 + (cos x)^2)^3 - 3(sin x)^2*(cos x)^2)((sin x)^2 + (cos x)^2)...

Asked by bibiloi on via web

• trigonometry math
Since x belongs to the range (pi,3pi/2), then x is located in the 3rd quadrant and the values of tangent function are positive. Since the tan function is a ratio between sine and cosine...

Asked by guteskind on via web

• trigonometry math
All we need to do is to substitute x by pi/4 in the expresison of the function: f(pi/4) = [cos (pi/4)]^2 - sin 2*(pi/4) f(pi/4) = [cos (pi/4)]^2 - sin (pi/2) We know that cos pi/4 = (sqrt2)/2 and...

Asked by anneenna on via web

• trigonometry math
We have 2*sin x*sin 3x - cos 4x = 0 (sin a)(sin b) = (1/2)(cos (a - b) - cos (a + b)) => 2*(sin a)(sin b) = cos (a - b) - cos (a + b) 2*sin x*sin 3x - cos 4x = 0 => cos (x - 3x) - cos 4x -...

Asked by errgonomix on via web

1 educator answer.

• trigonometry math
We have to solve 1 + cos x + cos 2x = 0 for x in the interval (0, pi) 1 + cos x + cos 2x = 0 => 1 + cos x + 2(cos x)^2 - 1 = 0 => cos x + 2(cos x)^2 = 0 => cos x( cos x + 2) = 0 => cos...

Asked by deuxtoi on via web

1 educator answer.

• trigonometry math
To find the value of sec (2x) if sin x = 3/5, cos x = 4/5, use the relation sin 2x = 2*sin x * cos x and (cos x)^2 = 1 - (sin x)^2 sin 2x = 2*sin x * cos x = 2*3/5 * 4/5 => sin 2x = 24/25 (cos...

Asked by leeaeel on via web

1 educator answer.

• trigonometry math
sin (x + y) = sin x* cos y + cos x * sin y It is given that sin x + cos y = 1/4 and cos x + sin y = 1/2 sin x + cos y = 1/4 square the two sides => (sin x)^2 + (cos y)^2 + 2*sin x*cos y = 1/16...

Asked by labrrat on via web

1 educator answer.

• trigonometry math
2x+pi/2 = arccos[cos(x-pi/2)] + 2k*pi 2x+pi/2 = (x-pi/2)+ 2k*pi We'll subtract pi/2; 2x = x - pi/2 - pi/2 + 2k*pi We'll subtract x: x = 2k*pi - pi x1 = pi(2k-1) 2x+pi/2 = -(x-pi/2)+ 2k*pi 2x+pi/2 =...

Asked by istetz on via web

• trigonometry math
We'll apply the identity: sin(arccos x) = sqrt(1 - x^2) (1) We'll put x = sqrt3/4 We'll raise to square both sides: x^2 = 3/16 We'll substitute x in the expression (1): sin(arccos sqrt3/4) = sqrt(1...

Asked by iszabelle on via web

• trigonometry math
Both equations are homogenous equations and they may be solved using tangent function. We'll start with the 1st equation: sinx+cosx=0 We'll divide by cos x: sin x*/cos x + 1 = 0 tan x + 1 = 0 tan x...

Asked by else9393 on via web

• trigonometry math
This problem requires the law of cosine to find out the angle V: KG^2 = VG^2 + KV^2 - 2VG*KV*cos V (1) Since the value of KV is missing, we could find it out, applying the law of cosine for the...

Asked by pavelpimen on via web

• trigonometry math
We'll shift 2 to the right side: -sec 4x = -2 We'll multiply by -1: sec 4x = 2 We'll apply the trigonometric identity: sec 4x = 1/cos 4x We'll re-write the equation: 1/cos 4x = 2 We'll put 4y = t...

Asked by gudeapp on via web

• trigonometry math
cot (x+1) = sqrt3 We'll take the arccot function both sides: x + 1 = arccot sqrt 3 + kpi x + 1 = pi/6 + kpi We'll subtract 1 both sides: x = pi/6 - 1 + kpi The solution of the equation is x = (pi/6...

Asked by margarethe on via web

• trigonometry math
We'll apply tangent functin to the sum of angles: a + b = pi/4 tan (a+b) = tan (pi/4) We'll apply the tangent identity: tan (a+b) = (tan a + tan b)/(1 - tan a*tan b) We'll replace tan(pi/4) by it's...

Asked by printsaltr on via web

• trigonometry math
Before solving the problem, we notice that the angle is foundin the 2nd quadrant, where the values of the function cosine are negative. Now, we'll start solving the problem. We'll use the double...

Asked by maisaphie on via web

• trigonometry math
We have sin x/ cos x = 2 We need to find (cos x)^2 sin x/ cos x = 2 => 2*sin x*cos x = 4*(cos x)^2 => sin 2x = 4*(cos x)^2 => (cos x)^2 = (sin 2x)/4 The value of (cos x)^2 = (sin 2x)/4

Asked by fortunee on via web

1 educator answer.

• trigonometry math
The equation to be solved is (cos x)^6 = 1 - (sin x)^6 (cos x)^6 = 1 - (sin x)^6 => (cos x)^6 + (sin x)^6 = 1 => (cos x)^2^3 + (sin x)^2^3 = 1 use a^3 + b^2 = (a + b)(a^2 - ab + b^2) =>...

Asked by oldcareer on via web

1 educator answer.

• trigonometry math
The equation given is 99sin^2x-101=-sin^2x. The number of roots of the equation have to be determined. 99(sin x)^2 - 101 = -(sin x)^2 => 100(sin x)^2 = 101 => (sin x)^2 = 101/100 => sin x...

Asked by magnet1qu3 on via web

1 educator answer.

• trigonometry math
We have to find x if (sin x)^2 = 1/4 (sin x)^2 = 1/4 => sin x = 1/2 and sin x = -1/2 x = arc sin (1/2) and x = arc sin (-1/2) arc sin (1/2) = 30 degrees and arc sin (-1/2) = -30 degrees. As the...

Asked by margarethe on via web

1 educator answer.

• trigonometry math
We know that sin a = sqrt3/2, so that arcsin (sqrt3/2) = a The sine function is positive in the 1st and the 2nd quadrants. a = 60 degrees = pi/3 radians (1st quadrant) a = 120 degrees = 2pi/3...

Asked by javiya on via web

• trigonometry math
We have to find the result of sin(pi/3) + sin(2pi/3) + sin(3pi/3) + sin(4pi/3) We use sin (pi/3) = (sqrt 3)/2 sin (2*pi/3) = sin (pi - pi/3) = sin (pi/3) = (sqrt 3)/2 sin (3*pi/3) = sin (pi) = 0...

Asked by sixpenpencil on via web

1 educator answer.

• trigonometry math
We have sin a + cos a = 1/3 Use the fact that sin 2a = 2*(sin a)(cos a) sin a + cos a = 1/3 square the right and left hand sides (sin a + cos a)^2 = (1/3)^2 => (sin a)^2 + (cos a)^2 + 2*(sin...

Asked by fromici on via web

1 educator answer.

• trigonometry math
We'll use the identity of triple angle: (sin x)^3 = (3sin x - sin 3x)/4 (cos x)^3 = (cos 3x + 3cos x)/4 We'll substitute th reltions above into equation: sin 3x*(3sin x - sin 3x)/4 + cos 3x*(cos 3x...

Asked by siteulove on via web

• trigonometry math
We need to simplify the expression (cos (x-y))^2 + (cos (x+y))^2 - cos 2x *cos 2y (cos (x-y))^2 + (cos (x+y))^2 - cos 2x *cos 2y => (cos x * cos y + sin x * sin y)^2 + (cos x * cos y - sin x *...

Asked by peux on via web

1 educator answer.

• trigonometry math
We'll re-write the term (cos z)^2 = [cos (x+y)]^2 cos (x+y) = cos x*cos y - sin x*sin y [cos (x+y)]^2 = (cos x*cos y - sin x*sin y)^2 We'll expand the square: [cos (x+y)]^2 = (cos x*cos y)^2 + (sin...

Asked by mikok on via web

• trigonometry math
We have to identify t if cos 2x + 2*(sin x )^2 + t = 0 cos 2x + 2*(sin x )^2 + t = 0 use cos 2x = 1 - 2*(sin x)^2 => 1 - 2*(sin x)^2 + 2*(sin x)^2 + t = 0 => 1 + t = 0 => t = -1 The...

Asked by lilfinance on via web

1 educator answer.

• trigonometry math
First, we'll re-write the term 9tan(-x), based on the fact that the tangent function is odd, so tg(-x)=-tgx => 9tan(-x) = -9 tan x The equation will become: 10tan x - 1 - 9 tan x = 0 We'll...

Asked by landishigh on via web

• trigonometry math
First, we'll move all terms to one side: -2(sin2x+1)/3-(sinx+cosx) = 0 We'll multiply by -3 the equation: 2sin2x + 2 + 3(sinx+cosx) = 0 We'll apply the double angle identity for sin 2x: sin 2x =...

Asked by museinspires on via web

• trigonometry math
To find the value of the sum, we'll create matching functions in the given sum. For this purpose, we'll substitute the value 0.5 by the equivalent function of the angle pi/6, namely sin pi/6 =...

Asked by rusrissa on via web

• trigonometry math
We'll use the double angle identity to re-write the term sin 6x: sin 6x = sin 2*(3x) = 2 sin 3x*cos 3x We'll re-write the equation, moving all terms to one side: 2 sin 3x*cos 3x + cos 3x = 0 We'll...

Asked by hallman on via web

• trigonometry math
We know that the cosine of double angle can be written as as the cosine of the sum of 2 like angles: cos(x+x) = cos x*cos x - sin x*sin x cos(x+x) = (cos x)^2 - (sin x)^2 (1) We'll write cos x in...

Asked by galbenusa on via web

• trigonometry math
We have to prove that 1+ sin x = cos( 90 - x) + cot 45 Let's start with cos( 90 - x) + cot 45 cos (90 - x) - cot 45 cos 45 = sin 45 = 1/sqrt 2 , cos (90 - x) = sin x => sin x + cot 45 => sin...

Asked by errgonomix on via web

1 educator answer.

• trigonometry math
We have to solve 3*cos(3x - 1) = 0 for x. 3*cos(3x - 1) = 0 => cos(3x - 1) = 0 => 3x - 1 = arc cos 0 => 3x - 1 = pi/2 + 2*n*pi and 3x - 1 = 3*pi/2 + 2*n*pi => 3x = pi/2 +1 + 2*n*pi and...

Asked by cartoffried on via web

1 educator answer.

• trigonometry math
For the beginning, we'll substitute the function tan pi/4 by it's value 1. We'll transform the sum into a product. For this reason, we'll have to express the value 1 as being the function sine of...

Asked by orlovolga on via web

• trigonometry math
The equation that has to be solved is (sin B)^2- 3 sin B + 2 =0 where 0 ≤ B ≤ 2π. (sin B)^2- 3*sin B +2 =0 => (sin B)^2- 2*sin B - sin B +2 =0 => (sin B)(sin B - 2 ) - 1( sin B - 2) =0...

Asked by alin-aquamarine on via web

1 educator answer.

• trigonometry math
We have to verify sin 25 + sin 35 = cos 5 sin 25 + sin 35 => 2* sin (25 + 35)/2 * cos 10/2 => 2* sin (60)/2 * cos 5 => 2* sin 30 * cos 5 sin 30 = 1/2 => 2 * (1/2) cos 5 => cos 5 This...

Asked by l0l1 on via web

1 educator answer.

• trigonometry math
We have to find the zeros of f(x) = sin x + cos x f(x) = sin x + cos x = 0 => sin x = -cos x => tan x = -1 x = arc tan (-1) In the interval (0, pi) , x = -pi/4 + pi = 3*pi/4 The required...

Asked by printsaltr on via web

1 educator answer.

• trigonometry math
We have to find x for 100*sin x - 99*cos x = 0 100*sin x - 99*cos x = 0 => 100*sin x = 99*cos x => sin x / cos x = 99/100 => tan x = 99/100 => x = arc tan(99/100) => x = 44.71...

Asked by lessoflot on via web

1 educator answer.

Showing 1–50 of 92